Proteasome-mediated degradation of keratins 7, 8, 17 and 18 by mutant KLHL24 in a foetal keratinocyte model: Novel insight in congenital skin defects and fragility of epidermolysis bullosa simplex with cardiomyopathy. Issue 8 (5th November 2021) - Logli, Elena; Marzuolo, Elisa; D'Agostino, Marco; Conti, Libenzio Adrian; Lena, Anna Maria; Diociaiuti, Andrea; Dellambra, Elena; Has, Cristina; Cianfanelli, Valentina; Zambruno, Giovanna; El Hachem, May; Magenta, Alessandra; et al.
Abstract: Epidermolysis bullosa simplex (EBS) with cardiomyopathy (EBS-KLHL24) is an EBS subtype caused by dominantly inherited, gain-of-function mutations in the gene encoding for the ubiquitin-ligase KLHL24, which addresses specific proteins to proteasomal degradation. EBS-KLHL24 patients are born with extensive denuded skin areas and skin fragility. Whilst skin fragility rapidly ameliorates, atrophy and scarring develop over time, accompanied by life-threatening cardiomyopathy. To date, pathogenetic mechanisms underlying such a unique disease phenotype are not fully characterized. The basal keratin 14 (K14) has been indicated as a KLHL24 substrate in keratinocytes. However, EBS-KLHL24 pathobiology cannot be determined by the mutation-enhanced disruption of K14 alone, as K14 is similarly expressed in foetal and postnatal epidermis and its protein levels are preserved both in vivo and in vitro disease models. In this study, we focused on foetal keratins as additional KLHL24 substrates. We showed that K7, K8, K17 and K18 protein levels are markedly reduced via proteasome degradation in normal foetal keratinocytes transduced with the mutant KLHL24 protein (ΔN28-KLHL24) as compared to control cells expressing the wild-type form. In addition, heat stress led to keratin network defects and decreased resilience in ΔN28-KLHL24 cells. The KLHL24-mediated degradation of foetal keratins could contribute to congenital skin defects in EBS-KLHL24. Furthermore, we observed that primary keratinocytes from EBS-KLHL24 patients undergo accelerated clonal conversion with reduced colony forming efficiency (CFE) and early replicative senescence. Finally, our findings pointed out a reduced CFE in ΔN28-KLHL24-transduced foetal keratinocytes as compared to controls, suggesting that mutant KLHL24 contributes to patients' keratinocyte clonogenicity impairment.